Persian cats - Quasha, Jennifer (New York : PowerKids Press, 2000)
Relates the history of the Persian cat and describes the physical and other characteristics of this quietest and least active of all cat breeds.
Includes index.
Keywords: Persian cat -- Juvenile literature; Persian cat; Cats